Modelling the subglacial hydrology of the former Barents Sea Ice Sheet - Gudlaugsson, Eythor (UiT Norges arktiske universitet, 2015)
Ice dynamics are strongly controlled by processes taking place at the interface between the ice and the underlying bed. In modern day ice sheets, up to 90% of mass is lost through fast-flowing corridors of ice, called ice streams. These are typically underlain by a thin layer of water and wet sediment, both of which promote fast flow. In recent years it has emerged that subglacial hydrology played an important role in the relatively fast disintegration of the Fennoscandian and the Barents Sea Ice Sheets (BSIS). The BSIS is a close historical analogue to the West Antarctic Ice sheet (WAIS) and understanding its demise could give important insight into the future evolution of the WAIS. In this study, we investigate the effect of subglacial water on the evolution of the Fennoscandian and the Barents Sea Ice Sheets. We do this by implementing a thin film model of water flow into an existing numerical ice sheet model and simulate the ice sheets growth and decay during the last glacial cycle. Additionally, we examine the influence of a subglacial lake on ice dynamics and isochrone layers within the ice. Basal water separates the ice and bed, softens the underlying sediments and greatly increases ice velocity. Including subglacial hydrology in numerical ice sheet models leads to less ice building up with time during glacial periods. Temperate areas of ice sheets are typically overestimated without it and deglaciation occurs more slowly. Subglacial water can form lakes underneath the ice that greatly affect its speed and thermal regime. Lake drainage can result in travelling waves at depth within isochrone layers, indicating the possibility of detecting past drainage events with ice penetrating radar. The effects of subglacial hydrology are important and accounting for them will be necessary in order to accurately estimate polar contributions to sea level change in the future.